Interfering with leukocyte trafficking in Crohn's disease. (February 2019) - Biswas, Sujata; Bryant, Robert V.; Travis, Simon
Abstract: The discovery of gut-specific leukocytes and the ability to modulate their function has been a groundbreaking development in the treatment of inflammatory bowel disease. Drugs target the interaction between lymphocytes and endothelial cells via integrins and their ligand cellular adhesion molecules. Safety, efficacy and sustainability of effect are key to this drug class, notwithstanding the association of natalizumab with fatal polyoma virus infection. Vedolizumab (2014) now licensed for the treatment of Crohn's disease around the world provides gut-specific immunosuppression. Targets for modulators of leukocyte trafficking include (examples in brackets) ICAM-1 (alicaforsen, efalizumab); MAdCAM-1 (PF-00547 659); α4 and related receptors (abrilumab, etrolizumab, natalizumab, vedolizumab); chemokine receptor CCR9 (vercirnon); and sphingosine 1-phosphate receptors (etrasimod, fingolimod, ozanimod). Oral and subcutaneous therapies are in development. The safety, efficacy and practice points of licensed drugs are discussed, in addition to initial results from therapeutic trials.